Pengaruh Penerapan Metode Latihan terhadap Kemampuan Servis Pendek Forehand Bulu Tangkis Siswa Kelas VII SMP Tunas Bangsa Mundu, Kabupaten Cirebon - Gery Adi Saputra; Suciati Rahayu Widyastuti (Indonesian Journal of Physical Education and Sport Science, 2023)
Study purpose. Mastery of basic badminton techniques, particularly the forehand short serve, is a crucial component for successful student performance. However, observations indicate that seventh-grade students' serving skills are still low, necessitating effective training methods to improve these skills. This study aimed to determine the effect of implementing a drill method on the forehand short serve skills of seventh-grade students at Tunas Bangsa Mundu Junior High School, Cirebon Regency. Materials and Methods. The study used a one-group pretest–posttest design with a quantitative approach. The sample size was 32 students (22 boys and 10 girls) selected using a purposive sampling technique. The test instrument measured forehand short serve accuracy, while data analysis used prerequisite tests (normality and homogeneity) and a paired-sample t-test to determine differences before and after treatment. Results. The results of the normality and homogeneity tests showed that the data were normally distributed and homogeneous. The paired-sample t-test yielded a Sig. (2-tailed) of 0.000 (<0.05), indicating a significant improvement in forehand short serve ability after implementing the drill method. Conclusion. The drill method has proven effective in improving the forehand short serve ability of seventh-grade students at Tunas Bangsa Mundu Junior High School. Structured and continuous practice repetitions help students master movement techniques more optimally.